A DECADE OF RESEARCH ON THE HISTORY OF RURAL EDUCATION IN BRAZIL (2012 - 2022) - Souza-Chaloba, Rosa Fátima [UNESP] (FapUNIFESP (SciELO), 2023)
This text is a bibliographical essay about the production of research on the history of rural education in Brazil, in the last decade, demarcating the reflection around the studies that have addressed the problems of elementary school and the formation and work of teachers for rural areas. The text begins by reconstituting the trajectory of the theme in the field of History of Education, highlighting the contribution of dissertations, theses and research projects. Then, it discusses some issues considered relevant to the debate on the theme, especially, the conceptual controversies, the historical production of the difference between urban and rural schools, the relations and disagreements between scholasticovists and advocates of the ruralization of education, the transnational circulation of ideas, proposals and models for rural education, the complex situation of lay teachers and the scope and limits of rural normal schools and regional normal courses.
UNA DÉCADA DE INVESTIGACIÓN SOBRE LA HISTORIA DE LA EDUCACIÓN RURAL EN BRASIL (2012 – 2022)
UNE DÉCENNIE DE RECHERCHES SUR L’HISTOIRE DE L’ÉDUCATION RURALE AU BRÉSIL (2012 – 2022)
Keywords: History of Rural Education; Rural Education; Rural Elementary Schools; Teacher Training for the Rural Environment